Electronic markets : challenges for the Stock Exchanges - Ho, Nan Yen (2008)
Aim: To assess the impact of business initiatives and technological trends on the roles of a stock exchange. Conclusion: Although business initiatives relate mainly to the operational role of an exchange, technological developments indicate and support an increase in the informational role.